Distribution of clinical signs and lesions in fluorotic cattle - RANJAN, R; SWARUP, D; BHARDWAJ, B (The Indian Journal of Animal Sciences, 2011)
Cattle population reared in fluoride endemic areas of district Nawada (Bihar) and Udaipur (Rajasthan) were examined critically for clinical signs and lesions of fluoride toxicity. In both areas, dental changes were the most common lesions, followed by bony exostosis and lameness. Hoof deformities, emaciation, hypogalactia, repeat breeding and anoestrus were other signs. Laboratory estimations revealed decrease in plasma calcium concentration and increase in alkaline phosphatase activity in fluorotic cattle. Plasma fluoride concentration in affected cattle population exceeded 1μg/ml.